Evaluation of diuretic activity of Paspalidium flavidum in rats - - Alamgeer; Muhammad Nasir Hayat Malik; Sajid Bashir; Abdul Qayyum Khan; Muhammad Naveed Mushtaq; Muhammad Rashid; Muhammad Akram; Sadia Samreen (Bangladesh Pharmacological Society, 2013)
This study was conducted to investigate the diuretic potential of aqueous methanolic extract of Paspalidium flavidum in rats. The extract at doses of 10, 30 50 and 100 mg/kg was administered intraperitoneally in acute diuretic model. Furosemide (10 mg/kg i.p) was used as standard drug. Total urine volume and urinary excretion of electrolytes were measured. Preliminary phytochemical tests were also performed using standard procedures. The extract exhibiteda significant dose dependent diuretic effect at all the doses when compared to control group. Urinary excretion of sodium was significantly increased by the extract while a significant increase in potassium excretion was only observed at higher doses. Phytochemical analysis illustrated that the extract contained compounds such as alkaloids, saponins, tannins, flavonoids, cardiac glycosides and reducing sugars. It is conceivable therefore that the aqueous methanolic extract of P. flavidum contain certain biologically active compounds that might be responsible for the diuretic activity.